The impact of natural disasters on income and poverty framework and some evidence from Philippine households - Israel, Danilo C.; Briones, Roehlano M. (2013)
This Policy Note provides a framework for analyzing the impact of natural disasters on household income and household poverty and empirically estimates the effects of natural disasters on household income using 2011 CBMS data for Pasay City, Metro Manila. It summarizes some of the results and findings of a recent study conducted by PIDS and funded by the Economic Research Institute for ASEAN and East Asia (ERIA).

The framework explains that after the physical impact, the social impact of a natural disaster on the households follows, which is determined by the physical impact, as well as household recovery resources or coping mechanisms, extra assistance, and sociodemographic and economic factors. Both the occurrence and frequency of typhoons and/or floods have significant negative effects on household per capita income as the case of Pasay City has shown.
Keywords: Natural disasters -- Economic aspects; Income; Poverty